Assessing a suitable extractant and critical limits of nickel in soil and plant for predicting the response of barley (Hordeum vulgare L.) to nickel grown in Inceptisols. Issue 20 (13th November 2018) - Kumar, Omkar; Singh, S.K.; Singh, A.P.; Yadav, S. N.; Latare, A.M.; Kumar, Maneesh
ABSTRACT: Nickel (Ni) is an essential element for plants. Abundant information exists on Ni toxicity in soil–plant system but not much is available on its critical level of deficiency (CLD) in soils and plants. Five chemical extractants were evaluated to find a suitable extractant for Ni in Inceptisol. Twenty-one soils having low to high levels of Ni were used to grow barley ( Hordeum vulgare L ). The amount of Ni extracted was correlated with Ni concentration and uptake by barley. The diethylene triamine penta acetic acid-calcium chloride (0.005 M DTPA-CaC12 ) was identified as the most promising soil extractant for Ni. The CLD of Ni for 0.005 M DTPA-CaC12 in soil was 0.22 mg kg −1 whereas in barley plant it was 2.14 mg kg −1 . Application of 7.5 mg kg −1 Ni in soil caused a significant increase in Ni concentration in the shoot of barley in all the soils irrespective of the initial Ni status.